Mathematical modelling of the Yeast Metabolic Cycle - Merchante González, A (2018)
The Yeast Metabolic Cycle (YMC) is an ultradian rhythm whose precise regulatory mechanism remains elusive. The YMC is a unique system that combines respiratory bursts with oscillations in both transcript levels and hundreds of metabolites in a tightly-controlled manner, creating an effective single-cell behavior that can be studied using sequencing techniques that require large quantities of cells. In this DPhil thesis I present a quantitative mathematical model of the YMC that is able to both describe the yeast synchronized metabolic activity and predict the outcome of several validating experiments.